If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2x + x + -2) = 4(x + 4) Reorder the terms: 2(-2 + 2x + x) = 4(x + 4) Combine like terms: 2x + x = 3x 2(-2 + 3x) = 4(x + 4) (-2 * 2 + 3x * 2) = 4(x + 4) (-4 + 6x) = 4(x + 4) Reorder the terms: -4 + 6x = 4(4 + x) -4 + 6x = (4 * 4 + x * 4) -4 + 6x = (16 + 4x) Solving -4 + 6x = 16 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -4 + 6x + -4x = 16 + 4x + -4x Combine like terms: 6x + -4x = 2x -4 + 2x = 16 + 4x + -4x Combine like terms: 4x + -4x = 0 -4 + 2x = 16 + 0 -4 + 2x = 16 Add '4' to each side of the equation. -4 + 4 + 2x = 16 + 4 Combine like terms: -4 + 4 = 0 0 + 2x = 16 + 4 2x = 16 + 4 Combine like terms: 16 + 4 = 20 2x = 20 Divide each side by '2'. x = 10 Simplifying x = 10
| 3y-14=17 | | 4x+52=5x+35 | | x^2/7=3 | | 43(x-2)=12 | | 5b-18=b+14 | | 3x-4=32+7x | | x+3=600 | | 23x+234+49834=25x | | 3x-x+8=20 | | 2-3x-y=0 | | 40+x=2*(x+14) | | 3x+4x+7=180 | | 3x-21+2x+16+2x+30+4x-13=287cm | | 3x+5+7=4x-14+3 | | x^4+6x^3+9x^2-16=0 | | xi+x+i=0 | | (((x-9500000)/2)/x)=0.1 | | 17.3+x=43.2 | | 661.2=870 | | (((9500000-x)/2)/9500000)=0.1 | | (((1100000-x)/2)/1100000)=0.1 | | (((1200000-x)/2)/1200000)=0.1 | | 3h+320=10h | | 390/2,600 | | s*7-40=79 | | =10a+3b-8a-4b | | (((1350000-x)/2)/1350000)=0.1 | | (((1250000-x)/2)/1250000)=0.1 | | -12r-20=28 | | (((1300000-x)/2)/1300000)=0.08 | | X-0.3x=140 | | x/20=9/5 |